Hichrom candida agar for identification of candida species - Baradkar V; Mathur M; Kumar S (Wolters Kluwer Medknow Publications, 2010)
Chromogenic media are frequently used in direct and rapid identification of yeasts because different Candida species produce unique colors on these media. We used 60 isolates of Candida species including 30 C. albicans, 10 C. parapsilosis, 11 C. glabrata, five C. tropicalis, and four C. dubliniensis, isolated from various clinical specimens, to evaluate the performance of HiChrome Candida agar. These strains had been identified by germ tube test, morphology on cornmeal agar, chlamydospore formation on tobacco agar and sugar assimilation tests. The sensitivity and specificity results were: C. albicans (96.55 and 96.42%); C. parapsilosis (80 and 98.03%), C. glabrata (90.90 and 88.23%), C. tropicalis (100 and 100%) and C. dubliniensis (60 and 96.55%) respectively. HiChrom Candida agaris medium has been useful and capable of presumptive, rapid identification of Candida species within 48 hours.